Evaluation of antimicrobial and non-steroidal anti-inflammatory treatments for BRD on health and welfare in fattening bulls: a cross-sectional study - Naod Thomas Masebo; Giovanna Marliani; Flavia Shannon Del Re; Laura Abram; Damiano Cavallini; Marco Di Pietro; Andrea Beltrame; Eliana Schiavon; Marilena Bolcato; Joaquin Hernandez Bermudez; Arcangelo Gentile; Joana G. P. Jacinto (Veterinary Quarterly)
Our study aimed to evaluate the effect of different treatments for BRD on health and welfare in fattening bulls. A total of 264 bulls were enrolled. Welfare was assessed on day 2 (T0) and day 15 (T1) after arrival. A decrease in the welfare level was observed from T0 to T1. All bulls were inspected clinically at T0 and T1 revealing an increase of skin lesions and lameness in T1. In both periods, a high incidence of respiratory disease was observed. A prevalence of 79.55% and 95.45% of Mycoplasma bovis using RT-PCR and culture at T0 and T1 respectively was observed. Blood samples were collected for haematology at T0 and T1. At T0, 36 animals were individually treated for BRD with an antimicrobial (IT), 54 received a metaphylactic treatment with tulathromycin (M), 150 received a metaphylactic treatment with tulathromycin plus a second antimicrobial (M + IT) whereas 24 were considered healthy and therefore not treated (NT). Additionally, 128 were treated with a non-steroid anti-inflammatory (NSAID). Neutrophils of M + IT were significantly higher than groups NT and M and the lymphocytes of M + IT were significantly lower than that of IT. White blood cells, neutrophils and N/L ratio of animals treated with an NSAID was significantly higher than that not treated. Lung inspection of 172 bulls at the abattoir indicated that 92.43% presented at least one lung lesion. A statistically significant effect of the NSAID treatment on the lung lesions was observed. Our findings indicate that BRD was a major welfare and health concern and evidence the difficulties of antimicrobial treatment of M. bovis.